Diferenças estratégicas de movimentação associadas à estrutura social em baleias jubarte, Megaptera novaeangliae (Borowski, 1781), através de dados de telemetria satelital - Ferreira, Anne Elise Landine (Universidade Federal de Juiz de Fora (UFJF), 2017)
Organisms movements may be considered a measurable behavioral response which outcomes from a combination of environmental factors, internal states and physiological restrictions. In this work, our goal was to evaluate and characterize the different patterns of movements of humpback whales (Megaptera novaeangliae Borowski, 1781), regarding gender and social role. Location data obtained with satellite telemetry were filtered and patterned by State - Space Model. The obtained route was divided in feeding area and migration route going from the isobath of 500 m. In this context, the turning angles and their frequencies to the right and to the left were calculated using ArcGIS 9.3 and the open source software R. The average angulations varied significantly, both to the left and right sides, in the comparative analysis of the areas regarding the whole group. Females with calf showed more significant differences to both directions, while males presented more prominent angles to the right side. The average frequencies for the moves facing right and left turned out to be significantly different when correlated between males, females and females with calf, in the reproduction areas, as well as the social role. Animals categorized as mothers presented more turns to both directions, when compared to companions and adult animals without calves. We have concluded that when the animals are in feeding area, they present more irregular movements and that females with calf are the ones with the highest movement variation. New tools should be associated with the satellite telemetry in order to obtain fine scale data providing a more accurate form to evaluate the animal movement. A movimentação dos organismos pode ser considerada uma resposta comportamental mensurável, resultante da combinação de fatores ambientais, estados internos e restrições fisiológicas. O objetivo deste trabalho foi avaliar e caracterizar os diferentes padrões de movimentação realizados pelas baleias jubarte (Megaptera novaeangliae), em relação ao gênero e ...